Design And Build an Aluminum Can Pressing Machine with A Capacity Of 85 Cans Using a Hydraulic System with Arduino control - Zulkifli, Muhammad Asyraf; Malik, Irawan; Akmal, Munawirul (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
An A used can collector in the countryside faces a challenge due to the extremely limited storage capacity of used products. Reducing the number of cans collected is crucial to maximize the available capacity. It is necessary for him to have a can press machine in order to make his work easier; hence, it is necessary to develop a can press machine that is more reasonably priced and has minimal running expenses. To simulate the arrangement of the press machine by determining the pressing mechanism, this final project is made beginning with the design of the press machine, selecting the type of material, which is ST37, the frame components of the size and type of frame thickness, and then assembling the frame through cutting, drilling, and welding methods. After the pressing mechanism has been determined and the appropriate results have been obtained, the project is complete. It is possible to hold up to 85 cans in the press room, which has a total space of 47,700 cubic centimetres, which is equivalent to 0.560 cubic centimetres per can. Upon pressing, the volume of the can is decreased to 14,850 cm3 for 85 cans, which is equivalent to 0.170 cm3 for each can. The overall reduction in can volume size is 32,850 cm3, which is equivalent to 0.386 cm3 for each can.